Characterizing the high-mass star forming region IRAS 18144–1723 through methanol maser observations. Issue 3 (23rd November 2022) - Khafagy, Esraa; Edris, K A; Shalabiea, O M; Bartkiewicz, A; Richards, A M S; Awad, Z
ABSTRACT: We introduce a study of the massive star forming region IRAS 18144–1723 using observations of the 6.7 GHz methanol maser line. Such regions are opaque at short wavelengths but can be observed through radio emission lines. In this study, we traced the kinematics of the source on milliarcsecond scales using the Multi-Element-Radio-Interferometer-Network (MERLIN). We found 52 maser spots in the LSR velocity range 45–52 km s −1, near the centre of the previously detected CO range of 21.3–71.3 km s −1, lying within ∼ 0${_{.}^{′′}}$ 5 of IRAS 18144–1723 'B', thought to be a young Class I protostar. Their distribution can be approximated as an ellipse, which, if it were rotating, would have its axis oriented south-east to north-west. The most probable morphology of the emitting regions is interaction between a disc and an outflow, possibly with a very large opening angle. The arcmin-scale CO outflow centred on source 'B' is oriented East–West, and the methanol masers do show the highest dispersion of velocity gradients in approximately this direction, so the kinematics are complex and suggest that more than one source may be responsible. We also tested kinematic models for a Keplerian disc or a simple bipolar outflow, but neither are compatible with the kinematics of the maser clumps and the characteristics of their internal velocities.